Kalanchoë Breeding: Past, Present and Future - Kahraman, Mehmet Uğur; Mendi, Yeşim Yalçın; Karabıyık, Şenay; Lütken, Henrik Vlk; Favero, Bruno Trevenzoli (Ornamental Horticulture, 2021)
Kalanchoë cultivars rank as one of the most sold potted ornamental plants in the world. Among its key features that sustain high market interest are the long flowering period, abundance of flowers, thick and glossy leaves, easy maintenance and less water requirement compared to other potted plants. In breeding studies of Kalanchoë, plants with different flower colors such as white, cream, yellow, orange, red, pink and purple were developed. Moreover, double-flowered cultivars (comprising a large number of petals), more compact and cultivars with larger flowers were also obtained. Novel morphological characteristics are always in high demand in the market of ornamental plants. Increasing the variation in the gene pool with different species played a major role in the development of these characteristics. Nowadays, not only potted cultivars are launched but also cut flower cultivars have been developed and presented to consumers. Besides conventional breeding and interspecific hybridization, biotechnological methods, which have a promising future, are used to develop morphological characteristics of Kalanchoë.